Notes relating to ’Haddo’s Hole’ in St Giles’ Church, Edinburgh - McCulloch, William T (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author explains the history of an iron door that was donated to the museum. The door was used to cover 'Haddo's hole', in St Giles Cathedral, where the Royalist Sir John Gordon Haddo was imprisoned before his execution in 1644. The article includes the expenses from the day of the execution and an illustration of 'The Maiden', the guillotine used to behead Haddo. Meeting notes for 10 June, 1861 are appended.